2010
DOI: 10.1186/1475-2875-9-22
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting fungus-induced larval mortality in Anopheles gambiae and Anopheles stephensi

Abstract: BackgroundEntomopathogenic fungi have shown great potential for the control of adult malaria vectors. However, their ability to control aquatic stages of anopheline vectors remains largely unexplored. Therefore, how larval characteristics (Anopheles species, age and larval density), fungus (species and concentration) and environmental effects (exposure duration and food availability) influence larval mortality caused by fungus, was studied.MethodsLaboratory bioassays were performed on the larval stages of Anop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 57 publications
1
52
0
2
Order By: Relevance
“…They also obtained a positive correlation between the fungal concentration and its lethality for the treated larvae, as has been observed in this study. Similarly, Bukhari et al (2010) used B. bassiana and M. anisopliae against larval stages of Anopheles gambiae and An. stephensi and found M. anisopliae to be more effective than the B. bassiana.…”
Section: Discussionmentioning
confidence: 99%
“…They also obtained a positive correlation between the fungal concentration and its lethality for the treated larvae, as has been observed in this study. Similarly, Bukhari et al (2010) used B. bassiana and M. anisopliae against larval stages of Anopheles gambiae and An. stephensi and found M. anisopliae to be more effective than the B. bassiana.…”
Section: Discussionmentioning
confidence: 99%
“…Metarhizium anisopliae and Beauveria bassiana are highly effective in reducing larval survival and adult emergence. When insecticide resistance is increasing, it is important to have a wider option of new biological and environmentally friendly control agents (Bukhari et al 2010). Similarly, F. oxysporum has shown potential in the control of larvae of C. quinquefasciatus and A. stephensi.…”
Section: Resultsmentioning
confidence: 99%
“…Fungal species have the potential to kill mosquitoes in the larval stage, and the mortality rate depends on the fungus species itself, larval stage targeted, larval density, and amount of nutrients available to the larvae. Increasing the concentration of fungal spore or reducing the exposure time to the spore did not show a proportional increase and decrease in mortality rate, respectively, because the spores clumped together (Bukhari et al 2010). We, therefore, are interested in the laboratory bioassays of F. oxysporum metabolites against the larvae of C. quinquefasciatus and A. stephensi.…”
Section: Introductionmentioning
confidence: 98%
“…Recent research has demonstrated that the entomopathogenic fungi Beauveria bassiana (Ascomycota: Cordycipitaceae) and Metarhizium anisopliae (Ascomycota: Clavicipitaceae) are able to shorten the lifespan of adult anopheline mosquitoes (Scholte et al 2005;Kanzok and Jacobs-Lorena 2006;Achonduh and Tondje 2008;Stevenson 2008), thus sparking interest in the use of such fungi as biological control agents. Furthermore, both B. bassiana and M. anisopliae have been reported to cause mortality of the larval stages of anopheline (Scholte et al 2004;Bukhari et al 2010) and aedine species (Silva et al 2004(Silva et al , 2005.…”
Section: Introductionmentioning
confidence: 99%